KERAGAMAN GENETIK, KEBUGARAN DAN INKOMPATIBILITAS REPRODUKSI Hemiptarsenus varicornis Girault (Hymenoptera: Eulophidae), PARASITOID LARVA Liriomyza huidobrensis (Diptera: Agromyzidae) - . Reflinaldon; Damayanti Buchori; Dwinardi Aprianto (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
Several experiments have been conducted to study genetic variation, fitness and reproductive incompatibility of H. varicornis from different geographic populations. Genetic variation from Pandai Sikek (PS), Alahan Panjang (AP) and Kayu Aro (KA) was analyzed by using random amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR) technique and the similarity of genetics measured using NTSys program. The fitness of female wasps such as longevity, fecundity and preoviposition was observed and then compared among those populations. Incompatibility in reproduction was determined by accounting of reproductive compatibility (RC) index in crossing of intra and interpopulation both of PS and AP. The results showed high genetic variation of H. varicornis among population from Alahan Panjang, Pandai Sikek and Kayu Aro with similarity coefficient of 30 to 70%. The best fitness showed the female wasps from Kayu Aro that was significantly different (P= 0.00) in longevity (24.60 ± 6.4 days), fecundity (63.6 ± 28.6 eggs) and parasitization (53.60%) but not significantly different (P=0.07) in number of the first day eggs (1.1 ± 1.4 eggs). Crossing of AP and PS indicated incompatibility in reproduction among the population.